Outcome-Focused Dance Movement Therapy Assessment Enhanced by iPad App MARA - Kim F. Dunphy; Tessa Hens (Frontiers in Psychology, 2018)
Healthcare and human services are increasingly required to demonstrate effectiveness and efficiency of their programs, with assessment and evaluation processes more regularly part of activity cycles. New approaches to service delivery, such as the National Disability Insurance Scheme (NDIS) scheme in Australia, require outcome-focused reporting that is responsive to the perspectives of clients. Eco-systematic approaches to service delivery and assessment consider the client as part of an interconnected web of stakeholders who all have responsibility for and contribute to their development and progress. These imperatives provide challenges for modalities for which there are not well-established assessment approaches. Dance movement therapists face particular difficulties in this respect, as they have few assessment tools that are practical for regular use. Existing dance movement therapy (DMT) assessment approaches largely do not yet prioritize input from clients. This article addresses these challenges in reporting a trial of iPad app MARA (Movement Assessment and Reporting App) developed for assessment in DMT. MARA is applied in a program for adults with intellectual disability (ID) over 16 weeks. Assessment data is gathered utilizing the app's features: two researcher-therapists undertake quantitative scoring that MARA aggregates into graphs, substantiated by qualitative note-taking, photos, and videos; and clients provide feedback about their progress stimulated by viewing photos and videos. A sample graph generated by MARA and supporting notes and a report drawn from data are provided. Responses to reports from program stakeholders (12 participants, 12 families, 11 center staff) gathered through interviews and focus groups are discussed, and researcher–therapists' reflections are detailed. The benefits of using MARA reported by researcher–therapists include strengthened capacity to focus on participant outcomes, assess efficiently, plan and make decisions for the program, and communicate participants' progress to stakeholders. Family members perceive reports drawn from data gathered in MARA to be useful in enabling better understanding of the DMT program and participant outcomes and potentially to support NDIS service planning. Managers perceive the potential value of data in these reports for quality control and resource decisions, while other staff confirm the therapists' perspective that reports offer the possibility of improved communication and collaboration between center staff.